Human case of bacteremia caused by Streptococcus canis sequence type 9 harboring the scm gene. (2017) - Taniyama, Daisuke; Abe, Yoshihiko; Sakai, Tetsuya; Kikuchi, Takahide; Takahashi, Takashi
Highlights: This is the first reported human case of bacteremia caused by Streptococcus canis having scm gene encoding M-like protein. The identity was based on similarity of its 16S rRNA and detection of the specific cfg gene encoding a co-hemolysin. This isolate was confirmed to be sequence type 9. This strain didn't have the erm(A), erm(B), or mef(A), macrolide resistance genes, but was not susceptible to azithromycin. Abstract: Streptococcus canis (Sc) is a zoonotic pathogen that is transferred mainly from companion animals to humans. One of the major virulence factors in Sc is the M-like protein encoded by the scm gene, which is involved in anti-phagocytic activities, as well as the recruitment of plasminogen to the bacterial surface in cooperation with enolase, and the consequent enhancement of bacterial transmigration and survival. This is the first reported human case of uncomplicated bacteremia following a dog bite, caused by Streptococcus canis harboring the scm gene. The similarity of the 16S rRNA from the infecting species to that of the Sc type strain, as well as the amplification of the species-specific cfg gene, encoding a co-hemolysin, was used to confirm the species identity. Furthermore, the isolate was confirmed as sequence type 9. The partial scm gene sequence harbored by the isolate was closely related to those of other two Sc strains. While this isolate did not possess the erm (A), erm (B), or mef (A), macrolide/lincosamide resistance genes, it was not susceptible to azithromycin: its susceptibility was intermediate. Even though human Sc bacteremia is rare, clinicians should be aware of this microorganism, as well as Pasteurella sp., Prevotella sp., and Capnocytophaga sp., when examining and treating patients with fever who maintain close contact with companion animals.